IDNLearn.com is the perfect place to get answers, share knowledge, and learn new things. Join our knowledgeable community to find the answers you need for any topic or issue.

Solving literal equations
Solving for y
-x + 3y = -6


Sagot :

Since y is the variable, x is considered here as a constant.

Then :

-x + 3y = -6

we add x in both left side and right side of the equation :

-x + x + 3y = -6 + x

3y = -6 + x

Then we divide both side by three :

3y / 3 = (-6+x) /3

y = (-6+x)/3

y = -6/3 + x/3

y= -2 + x/3

Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.